2017
DOI: 10.1038/ncomms14844
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the system xC−/glutathione axis selectively targets cancers with mutant-p53 accumulation

Abstract: TP53, a critical tumour suppressor gene, is mutated in over half of all cancers resulting in mutant-p53 protein accumulation and poor patient survival. Therapeutic strategies to target mutant-p53 cancers are urgently needed. We show that accumulated mutant-p53 protein suppresses the expression of SLC7A11, a component of the cystine/glutamate antiporter, system xC−, through binding to the master antioxidant transcription factor NRF2. This diminishes glutathione synthesis, rendering mutant-p53 tumours susceptibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
261
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(305 citation statements)
references
References 45 publications
28
261
1
1
Order By: Relevance
“…Likewise, direct depletion of cystine from plasma using an engineered cystine-degrading enzyme conjugate ( i.e., cyst(e)inase) arrests tumor growth and triggers cell death (Cramer et al, 2017). Agents that conjugate to glutathione, such as APR-246, as well as chemical or genetic inhibition of glutathione biosynthesis, disrupt tumor cell growth and induce a ferroptosis-like form of cell death (Liu et al, 2017). Typically, elevated levels of ROS are detected in response to perturbation of cysteine or glutathione metabolism and, where tested, cell death is prevented by antioxidant treatment.…”
Section: Ferroptosis Applications In Neoplastic Diseasesmentioning
confidence: 99%
“…Likewise, direct depletion of cystine from plasma using an engineered cystine-degrading enzyme conjugate ( i.e., cyst(e)inase) arrests tumor growth and triggers cell death (Cramer et al, 2017). Agents that conjugate to glutathione, such as APR-246, as well as chemical or genetic inhibition of glutathione biosynthesis, disrupt tumor cell growth and induce a ferroptosis-like form of cell death (Liu et al, 2017). Typically, elevated levels of ROS are detected in response to perturbation of cysteine or glutathione metabolism and, where tested, cell death is prevented by antioxidant treatment.…”
Section: Ferroptosis Applications In Neoplastic Diseasesmentioning
confidence: 99%
“…P53 is a tumour suppressor gene that is activated under different stress stimuli. P53 is involved in ferroptosis as a transcriptional repressor of SLC7A11, impairing cysteine import and promoting ferroptosis initiation . P53 is also involved in other programmed cell death processes.…”
Section: Main Textmentioning
confidence: 99%
“…In a recent study, Sato et al () showed that erastin, a ferroptosis (regulated necrotic cell death) inducer, synergized with cisplatin to increase its cytotoxicity in cancer cells via irreversible inhibition of Sx c − . In yet another interesting study, Liu et al () and Clemons, Liu, Duong, and Phillips () discussed the importance of therapeutic strategies for targeting mutant p53 protein. One such strategy involved suppressing function of xCT along with APR‐246, a small‐molecule known to restore sequence‐specific DNA binding of mutant p53 resulting in wild‐type p53 transcriptional activity and tumor‐suppressor function.…”
Section: Introductionmentioning
confidence: 99%
“…. In yet another interesting study, Liu et al (2017) and Clemons, Liu, Duong, and Phillips (2017) and investigated the role of activating transcription factor 4 (ATF4) which critically regulates the oxido-metabolic state in gliomas in the pathogenesis of temozolomide (TMZ) (first-line treatment for malignant gliomas)-resistance. The authors found out that the TMZ treatment led to increased expression of ATF4, xCT among others and the elevation of xCT as a consequential event of ATF4 activation.…”
mentioning
confidence: 99%